Recent Advances in the Development of Blue and Deep‐Blue Emitting Gold(I) and Gold(III) Molecular Systems. Issue 47 (5th November 2021) - Malmberg, Robert; Venkatesan, Koushik
Abstract: Highly efficient deep‐blue and blue emitting complexes remain one of the most back‐breaking challenges to overcome for organic light emitting diode (OLED) devices applications. Apart from the well‐investigated emitter systems involving iridium(III) and platinum(II) metal centres, gold(I) and gold(III) systems are gaining increasing attention as emitter systems with remarkable photoluminescence and electroluminescence properties. While most of the investigated Au(I) and Au(III) complexes emit in the green to yellow region, only a handful of examples show blue to deep‐blue emission. One of the main challenges to overcome are to develop ligand frameworks that lead to large triplet energies ( E T >2.7 eV), while maintaining high thermal and photostability of the complexes. A number of solutions involving the introduction of strong σ‐donors, sterically demanding ligands as well as bidentate and tridentate ligand frameworks were found in order to stabilise the gold(I) and gold(III) centres, respectively. This minireview summarises the recent advances of deep‐blue and blue‐emitting Au(I) and Au(III) complexes by highlighting the important milestones and the challenges yet to overcome. Abstract : Golden blue emitters : Organogold metal complexes have gained an immense interest due to their excellent triplet‐based luminescence properties and have been widely investigated for their use in organic light‐emitting diodes (OLEDs). While most of the reported gold complexes emit in the green and yellow part of the visible spectrum, only a handful of examples display blue and deep‐blue emission. In this minireview, the recent advances in the development of blue and deep‐blue emitting gold(I) and gold(III) complexes are summarised.